EXACT BOUNDARY CONTROLLABILITY OF AN INTEGRODIFFERENTIAL EQUATION - Leugering, Günter (Applied Mathematics and Optimization, 1987)
An integrodifferential equation of the Volterra type is considered under the action of anL2(0, T, L2(Γ))-boundary control. By harmonic analysis arguments it is shown that the controllability results obtained in [17] for the underlying reference model associated with a trivial convolution kernel, carry over to the model under consideration without any smallness assumption concerning the memory kernel. <aside class="ArticleNote ArticleNoteCommunicatedBy"> Communicated by A. V. Balakrishnan </aside>